A novel real-time demand side management scheme for the addition of electrical vechicles to the future grid - Naila Zareen, 1979-, author; Mohd. Wazir Mustafa, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2016